Pengaruh Kredibilitas Daya Tarik dan Kepercayaan terhadap Minat Pembelian Sunscreen Azarine di Kota Yogyakarta - Cardoso, Juliarsi; Prasojo, Eko (CV. Kurnia Grup, 2024)
This study aims to determine the partial and simultaneous influence of Credibility, Attractiveness and Trust on Interest in Purchasing Suncreen Azarine in Yogyakarta City. This study uses a type of quantitative research. The population in this study is All Azarine Sunscreen Users in Yogyakarta City. The sample in the study was 198 respondents. The sample determination technique was taken using purposive sampling, a method of determining samples with the consideration of the researcher which was then processed using SPSS. The data collection technique in this study uses a questionnaire. The instrument testing technique in this study uses validity and reliability. And the data analysis techniques in this study used classical assumptions, multiple linear regressions, determination coefficients and hypothesis tests. The results of this study are as follows. Partially, Credibility has a significant effect on the interest in Purchasing Azarine Sunscreen by marking a t-count value of 2.206 greater than the t-table of 1.972. Partially, Attractiveness had a significant effect on the interest in Purchasing Sunscreen Azarine by marking the t-count value of 0.324 smaller than the t-table 1.972. Simultaneously, Credibility, Attractiveness and Trust have a significant effect on the interest in Purchasing Azarine Sunscreen. This study aims to determine the partial and simultaneous influence of Credibility, Attractiveness and Trust on Interest in Purchasing Azarine Sunscreen in Yogyakarta City.